ANALISIS POSTUR KERJA PADA MEKANIK BENGKEL SEPEDA MOTOR HIDROLIK “X” DAN NON-HIDROLIK “Y” KOTA SEMARANG - Adlina Rahmadini Adzhani; Ekawati Ekawati; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Work postures are various positions of the body during work activities. Work postures on mechanics motorcycle have risks musculoskeletal disorders (MSDs). It is associated with awkward postures, duration, and frequency when performing daily activities. Activities of vehicle maintenance consist of six steps, including measuring, disassembling, repairing, replacing, and adjustment. The purpose of this research was to analyze the work postures with Rapid Entire Body Assessment (REBA) methods on “X” hydraulic motorcycle mechanics and “Y” non-hydraulic motorcycle mechanics in Semarang. This type of research was descriptive. The subjects were seven vehicle maintenance activities in both types of the workshops and the respondents were 8 mechanics for filling out the questionnaire of Nordic Body Map. The results showed that 86 percent (right side) and 71 percent (left side) activities in “X” hydraulic motorcycle shop and 57 percent (right and left side) activities in “Y” non-hydraulic motorcycle shop had a score of medium risk level. In addition, there were 14 percent (right side) and 29 percent (left side) activities in “X” hydraulic motorcycle shop and 43 percent (right and left side) activities in